Convergence Insufficiency/Divergence Insufficiency Convergence Excess/Divergence Excess: Some Facts and Fictions - Edward Khawam; Bachir Abiad; Alaa Boughannam; Joanna Saade; Ramzi Alameddine (Case Reports in Ophthalmological Medicine)
Great discrepancies are often encountered between the distance fixation and the near-fixation esodeviations and exodeviations. They are all attributed to either anomalies of the AC/A ratio or anomalies of the fusional convergence or divergence amplitudes. We report a case with pseudoconvergence insufficiency and another one with pseudoaccommodative convergence excess. In both cases, conv./div. excess and insufficiency were erroneously attributed to anomalies of the AC/A ratio or to anomalies of the fusional amplitudes. Our purpose is to show that numerous factors, other than anomalies in the AC/A ratio or anomalies in the fusional conv. or divergence amplitudes, can contaminate either the distance or the near deviations. This results in significant discrepancies between the distance and the near deviations despite a normal AC/A ratio and normal fusional amplitudes, leading to erroneous diagnoses and inappropriate treatment models.